The exiles in love - McKay, Hilary (London: Hodder Children's, 2007)
Help! Love strikes the Conroy sisters! First Ruth fancies the school bus-driver, but she and Naomi soon fall for the Temporary English Teacher. Then all four sisters are bewitched by the charms of Philippe ... The delightful finale to the award-winning Exiles series.
Keywords: Children's stories